Trends in recorded deaths involving antipsychotics: The role of deprivation, ethnicity, and regional disparities - Muhammad Umair Khan; Syed Shahzad Hasan (PLoS ONE, 2026)
Objective The relationship between antipsychotic use and mortality remains uncertain, with evidence suggesting both potential risks and benefits. This study aimed to examine trends in recorded deaths involving antipsychotics in England and to explore regional, socioeconomic, and ethnic variation in these patterns. Methods A population-level analysis of NHS prescription data (2015–2023) across seven regions of NHS England used linear regression and generalised additive models (GAMs) to explore associations between recorded deaths involving antipsychotics and deprivation, ethnic density, and regional variation. Results Recorded deaths involving antipsychotics increased from 10.33 to 13.85 deaths per million prescription items between 2015 and 2023 (p < 0.01), with an annual increase of 3.56%. Regional analysis showed significant disparities, with the highest increase observed in London (9.99%, 95%CI: 9.50–10.48) and a decrease was observed in the Midlands (−2.06%, 95%CI: −2.71 – −1.41). Deprivation was significantly associated with increased mortality (p < 0.01), while regions with higher Asian density exhibited lower mortality rates (p = 0.01). Conclusions Recorded deaths involving antipsychotics have increased over the past decade, with considerable regional disparities. Deprivation remains a key driver of mortality risk. While antipsychotics have well‑established clinical benefits in the management of severe mental illness, these findings highlight the need for strengthened prescribing safety, improved monitoring, and equity‑focused interventions to reduce preventable deaths.